Deciphering the weathering processes using environmental mineralogy and geochemistry: Towards an integrated model of laterite and podzol genesis in the Upper Amazon Basin - Fritsch, Emmanuel; Balan, Etienne; Do Nascimento, Nadia Regina [UNESP]; Allard, Thierry; Bardy, Marion; Bueno, Guilherme; Derenne, Sylvie; Melfi, Adolpho Jose; Calas, Georges (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
This article reports major results from collaborative research between France and Brazil on soil and water systems, carried out in the Upper Amazon Basin. It reveals the weathering processes acting in the partly inundated, low elevation plateaus of the Basin, mostly covered by evergreen forest. Our findings are based on geochemical data and mineral spectroscopy that probe the crystal chemistry of Fe and Al in mineral phases (mainly kaolinite, Al- and Fe-(hydr)oxides) of tropical soils (laterites). These techniques reveal crystal alterations in mineral populations of different ages and changes of metal speciation associated with mineral or organic phases. These results provide an integrated model of soil formation and changes (from laterites to podzols) in distinct hydrological compartments of the Amazon landscapes and under altered water regimes. (C) 2010 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Crystal chemistry of Al and Fe; Kaolinite; Fe-oxides; Organo-metallic complexes; Laterites podzols; Amazon Basin